Local Delivery of Metronidazole-loaded N-Trimethyl Quaternary Ammonium Chitosan Nanoparticles for Periodontitis Treatment - Garg, Kritika; Tirgar, Pravin (Current Drug Therapy, 2022)
Background: Recent findings suggest that chitosan has shown antibacterial activity acting through various mechanisms, but when the amine group in chitosan is converted to quaternary ammonium compound, the antibacterial activity of chitosan is elevated due to the increase in its solubility in an acidic environment. Objectives: The purpose of this study was to formulate and standardize metronidazole-loaded Ntrimethyl quaternary ammonium chitosan nanoparticles for the treatment of periodontitis. Method: N-trimethyl quaternary ammonium chitosan derivative was synthesized, and nanoparticles (NPs) were prepared by ionic gelation methodology followed by 32 full factorial designs. Particle size, zeta potential, polydispersity index (PDI), surface morphology, thermal properties, in vitro drug release as well as antimicrobial activity, stability study, ex vivo, and acute toxicity of NPs were evaluated. Results: The optimized batches of NPs were in the size range of 150 to 237 nm with a mean size of 117.01 ± 0.03 nm. Entrapment efficiency (EE) of 81.45 ± 0.03 % was obtained with a zeta potential (mV) of 28.19 ± 0.03 mV. Almost 98.97 ± 7.17% of the drug was released within 24 hours in vitro to obtain a sustained release drug; the optimized batches exhibited a smooth surface with appreciable in vitro, ex vivo antibacterial, and acute toxicity, and it was found that the formulation could be stored for up to 6 months. Conclusion: The present study revealed that metronidazole-loaded N-trimethyl quaternary ammonium chitosan nanoparticles exhibit enhanced antibacterial activity against periodontal infections.
Keywords: 32 full factorial design